Sistem Pelaporan Jumlah Penduduk Desa Kembangseri Kecamatan Bermani Ilir Kabupaten Kepahiang Provinsi Bengkulu - Sapri Sapri; Hermawansa Hermawansa ((JurTI) Jurnal Teknologi Informasi, 2020)
Abstract - Villagers are groups of relatively small areas within an area that are bound by applicable regulations and interact with each other continuously or continuously. Population development will be influenced by the number of babies born, the number of deaths, out-migration (moving), and in-migration (incomers). The problem in this study is how the Population, Death, Birth, and Outgoing Migration (migrants) Reporting System uses a programming language. The benefits of research are to facilitate the population reporting system, make it easier for village officials to record population numbers, births, deaths, in-migration, and out-migration quickly and effectively, make it easier for people to get information on population numbers, births, deaths, out-migration, and in-migration (comer). The purpose of this research is to create new technology in the world of the village government with a special programming language (Visual Basic.Net). in the village government of Kembang Seri, Bermani Ilir District, Kepahiang Regency, Bengkulu Province. Literature research methods and primary and secondary data collection methods in providing public services to the community require a system that can help local governments, especially in Kembangseri Village, Bermani Ilir District, Kepahiang Regency, Bengkulu Province in terms of a Reporting system for population, births, and deaths, out-migration (moving) and in-migration (newcomers) using a special programming language (Visual Basic.Net).Keywords: Birth, Death, Outgoing Migration, and Inward Migration. Abstrak - Penduduk Desa adalah kelompok wilayah yang relatif kecil  di dalam suatu wilayah yang terikat oleh aturan-aturan  yang berlaku dan saling berinteraksi satu sama lain secara    terus  menerus  atau  kontinu. Perkembangan penduduk akan dipengaruhi oleh jumlah bayi yang lahir,  jumlah kematian, migrasi keluar (pindah) dan migrasi masuk (pendatang).  Adapun masalah dalam penelitian ini adalah bagaimana cara Sistem Pelaporan Jumlah Penduduk, Kematian, kelahiran, migrasi keluar (pindah)  migrasi masuk (pendatang) dengan menggunakan bahasa pemrograman. Manfaat penelitian untuk memudahkan sistem pelaporan jumlah penduduk, Memudahkan Perangkat desa mendata jumlah Penduduk, kelahiran, kematian, migrasi masuk dan migrasi keluar dengan cepat dan efektif, Memudahkan masyarakat untuk mendapatkan Informasi jumlah penduduk, Kelahiran, kematian, migrasi keluar (pindah) dan migrasi masuk (pendatang). Tujuan penelitian ini untuk membuat teknologi baru dalam dunia pemerintahan desa dengan bahasa pemrograman khusus (Visual Basic.Net). pada pemerintahan desa Kembang Seri Kecamatan Bermani Ilir Kabupaten Kepahiang Provinsi Bengkulu.Metode penelitian Kepustakaan dan Metode Pengumpulan data Primer dan Sekunder dalam penyelenggaraan pelayanan publik kepada masyarakat membutuhkan Suatu sistem yang dapat membantu Pemerintah daerah khususnya di Desa Kembangseri Kecamatan Bermani Ilir Kabupaten Kepahiang Provinsi Bengkulu dalam hal  Sistem Pelaporan jumlah penduduk,  kelahiran  dan kematian, migrasi keluar (pindah) dan migrasi masuk (pendatang) dengan menggunakan bahasa pemrograman khusus (Visual Basic.Net).Kata Kunci: Kelahiran, Kematian, Migrasi Keluar dan Migrasi Masuk.